Donkeys - Noonan, Diana; Black, Don (Nelson Australia South Melbourne, Vic., 1994)
Donkeys by Diana Noonan is an informative and engaging children$1 (Bs book that explores the lives and characteristics of donkeys. Through vivid illustrations and accessible text, the book introduces young readers to the physical features, behaviors, and various breeds of donkeys. It highlights their importance as working animals, their roles in different cultures, and their gentle nature. The narrative encourages an appreciation for these often-overlooked animals, fostering a sense of empathy and understanding. With its blend of fun facts and engaging storytelling, Donkeys serves as an excellent resource for children interested in animals and the natural world.s